Optimizing Unmanaged Inherited Assets in Indonesia: A Review of The Waqf Model and Challenges in Its Development - Nisa', Mir'atun; Sukmana, Raditya; Arifin, Samsul (e-Journal Ekonomi Bisnis dan Akuntansi, 2025)
The inheritance system in Muslim societies has an urgent social, spiritual, and economic impact. There is not a single human being who will not be involved in inheritance matters. Because for every person who dies, the main thing that must be taken care of is the issue of inheritance, whether large or small amounts are left behind. However, it cannot be denied that there will be cases where an heir has no heirs so that after his death, the inherited property is ownerless. In this case, the state is responsible for its management through Baitul Maal or an appointed agency. The methodology used in this research is a literature study of relevant documents and journals on related topics. Through this approach, this research seeks to search for and combine various existing data and information to gain a comprehensive understanding of efforts to manage unkempt inheritance in Indonesia, its optimization model through waqf instruments, and opportunities and challenges for its development in the future.